Emerging Approach: Reduce Histamine Poisoning with Diamine Oxidase. Issue 3 (25th February 2014) - Naila, Aishath; Flint, Steve; Fletcher, Graham C.; Bremer, Phil J.; Meerdink, Gerrit
Abstract Rihaakuru is a cooked fish paste from the Maldives, consumed as a condiment with rice and other food. One of our studies confirmed that Rihaakuru contained up to 10 different biogenic amines, with histamine in excess of 500 ppm (n = 28). This may cause histamine poisoning, with symptoms such as skin rashes, vomiting and fever, thus making it a food security issue in the Maldives. Another study by us developed a regression model that predicted the rate and amount of histamine removal by diamine oxidase (DAO) under varied pH and salt concentrations in the tuna soup used to manufacture Rihaakuru. Based on the results of these studies, a conceptual design in producing histamine‐free Rihaakuru is described in this paper. This conceptual design could be used as a guideline in the actual production of histamine‐free Rihaakuru. Histamine‐free Rihaakuru could be a potential export containing high protein and omega‐3. Practical Applications Rihaakuru is a fish paste that is rich in protein, minerals and contains omega 3. However, Rihaakuru can contain more than 500 ppm histamine that may cause food poisoning. This histamine originates from poor quality raw fish used to manufacture this product. The manufacture of Rihaakuru is seen as a way of using poor quality fish. Rihaakuru is generally stable in terms of bacterial deterioration and the only issue is the high histamine level. This research demonstrated on a novel method to prevent histamine food poisoning using diamine oxidase, to degrade the histamine in the fish soup during the manufacture of Rihaakuru. This enables the manufacture of histamine free‐Rihaakuru and has the potential to be applied to other foods containing histamine.